RNA Polymerase II CTD Modifications: How Many Tales From a Single Tail. Issue 5 (May 2014) - Napolitano, Giuliana; Lania, Luigi; Majello, Barbara
<x xml:space="preserve">Abstract</x> Eukaryote's RNA polymerases II (RNAPII) have the feature to contain, at the carbossi‐terminal region of their largest subunit Rpb1, a unique CTD domain. Rpb1‐CTD is composed of an increasing number of repetitions of the Y1S2P3T4S5P6S7 heptad that goes in parallel with the developmental level of organisms. Because of its composition, the CTD domain has a huge structural plasticity; virtually all the residues can be subjected to post‐translational modifications and the two prolines can either be in cis or trans conformations. In light of these features, it is reasonable to think that different specific nuances of CTD modification and interacting factors take place not only on different gene promoters but also during different stages of the transcription cycle and reasonably might have a role even if the polymerase is on or off the DNA template. Rpb1‐CTD domain is involved not only in regulating transcriptional rates, but also in all co‐transcriptional processes, such as pre‐mRNA processing, splicing, cleavage, and export. Moreover, recent studies highlight a role of CTD in DNA replication and in maintenance of genomic stability and specific CTD‐modifications have been related to different CTD functions. In this paper, we examine results from the most recent CTD‐related literature and give an overview of the general function of Rpb1‐CTD in transcription, transcription‐related and non transcription‐related processes in which it has been recently shown to be involved in. J. Cell. Physiol. 229: 538–544, 2014. © 2013 Wiley Periodicals, Inc.